К вопросу о мартириях ранневизантийского Херсона - Сорочан, С.Б. (Археологический альманах, 2012)
In the article made to collect all items of information about sacral monuments of Early Byzantine Cherson, which can be ranked as number of martyrs. Their general features are allocated. It is possible to speak about two kinds of such structures by number about ten, connected with burial, relics of martyr or with a place, where there was a miracle accomplished by a God. To first concern the martyr of Uvarov’s basilica (catholicon of St. Apostols), in a “cave temple”, in a monastery of St. Leontius, in the “sacred cemetery” outside city and on an island in Kazachja bay. Last two were connected with agyasmos or thyalos with curative water. To the second kind concerns large tetrakonchos in western part of city. The constructions of these martyrs were begun not earlier than end of IV century and were held mainly in second half of VI century. Most late has arisen after 861 AD. The majority martyrs was connected to reverence of local sacred peoples, well known in agiography of Cherson (first byshofs of city), and only one (St.. Clement of Rome) has acquired in IX century the common Byzantian status of reverence.